Histamine Induces Alzheimer's Disease-Like Blood Brain Barrier Breach and Local Cellular Responses in Mouse Brain Organotypic Cultures. (30th November 2015) - Sedeyn, Jonathan C.; Wu, Hao; Hobbs, Reilly D.; Levin, Eli C.; Nagele, Robert G.; Venkataraman, Venkat
Abstract : Among the top ten causes of death in the United States, Alzheimer's disease (AD) is the only one that cannot be cured, prevented, or even slowed down at present. Significant efforts have been exerted in generating model systems to delineate the mechanism as well as establishing platforms for drug screening. In this study, a promising candidate model utilizing primary mouse brain organotypic (MBO) cultures is reported. For the first time, we have demonstrated that the MBO cultures exhibit increased blood brain barrier (BBB) permeability as shown by IgG leakage into the brain parenchyma, astrocyte activation as evidenced by increased expression of glial fibrillary acidic protein (GFAP), and neuronal damage-response as suggested by increased vimentin-positive neurons occur upon histamine treatment. Identical responses—a breakdown of the BBB, astrocyte activation, and neuronal expression of vimentin—were then demonstrated in brains from AD patients compared to age-matched controls, consistent with other reports. Thus, the histamine-treated MBO culture system may provide a valuable tool in combating AD.